Absence of Wharton's jelly: case report - Oliveira, Cristiano Claudino [UNESP]; Dufloth, Rozany Mucha; Coelho, Kunie Iabuki Rabello [UNESP] (Sociedade Brasileira de Patologia Clínica Sociedade Brasileira de Patologia Sociedade Brasileira de Citopatologia, 2014)
There are few reports in the literature of the absence of Wharton's Jelly. Here we report the seventh case in a primigravida, 22 years old, admitted after vaginal delivery of stillborn. The umbilical cord have a long segment with disruption of cord structures and the three blood vessels were completely separated from each other, with a minimum amount of Wharton's jelly remaining around each vessel. The absence of Wharton' jelly is associated with fetal distress, intrauterine growth restriction, and fetal death. Quantitative/qualitative studies of Wharton's jelly represent an open field of research for possible correlations with obstetric conditions and fetal deaths.

Na literatura, há poucos relatos sobre a ausência de geleia de Wharton. Relatamos o sétimo caso em uma primigesta de 22 anos, admitida após parto vaginal de feto natimorto. O cordão umbilical apresentava longo segmento com esfacelo da geleia e três vasos sanguíneos completamente separados uns dos outros, com mínima quantidade de geleia de Wharton remanescente ao redor de cada vaso. Ausência de geleia de Wharton associa-se a estresse, restrição de crescimento e óbitos fetais. Estudos quantitativos/ qualitativos sobre a geleia de Wharton representam campo de pesquisa aberto para possíveis correlações com condições e doenças obstétricas e óbitos fetais.
Ausência da geleia de Wharton: relato de caso
Keywords: Umbilical cord; Pathology; Wharton's jelly; Fetal death; Cordão umbilical; Patologia; Geleia de Wharton; Óbito fetal